Pneumonia Incident in Toddler Related to House Environment and Other Factors - Indriani K Sumadikarya; Heriyanto Heriyanto; Dewi Iriani; Reagan Sanjaya Purnama (Jurnal MedScientiae, 2023)
Pneumonia is the most problematic disease that happened in toddler that can lead to death. Data based on depkes, profil kesehatan 2010 population characteristic with the highest pneumonia happened in toddler (11,2%). The goal of this research is to know the relation between house environment and other factors in incident of pneumonia in Grogol petamburan, West Jakarta approach on 2020. The design of this study is cross sectional. Population sample used on this study is toddler who lived in Grogol petamburan, West Jakarta. The research subjects are 50 samples the technique used to gather samples using simple random sampling. The analysis used was Chi Square. the results shows that pneumonia as many as 36 people (72%) and not pneumonia as many as 14 people (28%). ASI exclusive (p=0.021), nutrient status (p=0.034), house environment (ventilation , sum of the people in the house)(p=0.017) these are the factors that have relation to cause pneumonia in toddler while age (p=0.970), immunization status (p=0.595), parents education (p=0.05), cigarette (p=0.503) don’t have any relation to cause pneumonia in toddler